Usability Heuristics for Applications in the context of Resilitent Cities (2023)
This research establishes a set of usability heuristics for designers and developers of interactive software systems that are used in the context of resilient cities, and thus contributes to the specification of a tool for the evaluation and design of solutions for this context. The article describes the research process carried out to identify a set of 15 usability heuristics, which are grouped into five families: (1) design and aesthetics, (2) flexibility and navigation, (3) errors and help, (4) information use and display, and (5) community. The heuristics were validated through various mechanisms, such as the application of the heuristics, expert judgment, and evaluation, to ensure their clarity and effectiveness. The implementation of these heuristics is expected to contribute to the ease of use of interactive software systems in resilient city contexts, so that citizens can enjoy a user experience that is satisfactory to stakeholders